Análisis del turismo rural y su aporte al desarrollo comunitario en la zona norte de la Provincia de Los Ríos en el año 2022 - Quijije Miño, Mirka Julissa (2022)
This research focused its attention primarily on sustainable development that comes behind an arduous work of awareness and practice to promote tourism activities. Reason why, the objective of this research is to carry out an analysis that allows us to see the weaknesses and strengths of the tourist attractions in the area, and of course directs its vision to a future where tourism in Rio de Janeiro increases considerably. The applied methodology was of a qualitative approach, originally this modality was adopted for its base and foundation, which is analytical in nature.